Segmentation of Nastaliq script for OCR - Sattar, Sohail A.; Haque, Shamsul; Haque, Mahmood K.Haque Pathan (2009)
In this paper we have presented a novel segmentation technique for the implementation of an OCR (Optical Character Recognition) for printed Nastalique text, a calligraphic style of Urdu which uses the Arabic script for its writing.OCR for many of the world major languages have been developed and are being used but at present an OCR for Nastalique is not available and the published research on Nastalique OCR, Urdu OCR or even on any area of Urdu computing is almost non-existent, the reason being the challenges that the Nastalique style poses for its optical recognition. We used Matlab 7 for our experimentation the results are reported in this paper which are very encouraging.